Cytokine profiles of Necator americanus and Plasmodium falciparum co-infected patients in rural Ghana. Issue 4 (December 2019) - Amoani, Benjamin; Adu, Bright; Frempong, Margaret T.; Sarkodie-Addo, Tracy; Victor Nuvor, Samuel; Abu, Emmanuel Kwasi; Harrison, Lisa M.; Cappello, Michael; Gyan, Ben; Wilson, Michael D.
Highlights: Co-infection of hookworm with P. falciparum modulates blood parasitemia levels. Cytokine levels were higher in the parasite infected individuals. Serum eotaxin level correlate negatively with hookworm intensity. Deworming drug treatment alters cytokine profiles in hookworm infected subjects. Abstract: Background: Necator americanus (hookworm) and Plasmodium falciparum co-infections are common in endemic communities in rural Ghana. Human immune responses to P. falciparum and hookworm are complex, and the dynamics of cytokine levels and effector mediators are poorly understood. This study aimed to determine the effect of hookworm and P. falciparum co-infection on parasite intensities and cytokine profiles in individuals before and after deworming drug treatment. Methods: In this cross-sectional study conducted in the Kintampo North Municipality of Ghana blood and stool samples were analyzed from 984 participants (aged 4–88 years). Stool samples were collected at baseline from all participants and examined for the presence of hookworm using the Kato-Katz method. Blood and stool samples were analysed again two weeks after albendazole treatment of hookworm infected individuals. Malaria parasitaemia was estimated by light microscopy and P. falciparum -specific 18S rRNA gene PCR method used for species identification. Serum levels of circulating cytokines interleukins -5, -10 (IL-5, IL-10), tumor necrosis factor [TNF]-α, and eotaxin [CCL11] were determined using ELISA based methods. Results: Malaria parasitaemia was significantly reduced in hookworm and P. falciparum co-infected individuals (p = 0.0018) while hookworm intensity was similar between groups. IL-10 level was significantly higher in the co-infected individuals (39.9 ± 12.2 pg/ml) compared to the single infected or the uninfected group (10.7 ± 7.6 mg/ml). IL-5 level was higher in the hookworm only infected individual. TNF-α levels were higher in all infected groups compared to the uninfected controls. CCL11 levels were significantly higher in subjects infected with hookworm only or co-infected with hookworm and P. falciparum. There was a significantly negative correlation (rs = −0.39, p = 0.021) between hookworm eggs per gram of stool and CCL11 levels in the group mono-infected with hookworm which was not affected by treatment. Treatment with albendazole led to a significant reduction of TNF-α (p = 0.041), IL-5 (p = 0.01) and IL-10 (p = 0.001) levels. Conclusion: This study shows that in the absence of other helminths, co-infection of hookworm with P. falciparum may modulate blood parasitemia levels and cytokine responses. Data also show that deworming drug treatment alters these cytokine profiles in hookworm infected subjects. Future studies to elucidate the potential mechanisms underlying these observations should include an assessment of parasite specific cellular responses.